Infeksi Bean common mosaic virus pada Umur Tanaman Kacang Panjang yang Berbeda - Hamdayanty Hamdayanty; Tri Asmira Damayanti (Jurnal Fitopatologi Indonesia, 2014)
Bean common mosaic virus (BCMV) is one of the most important virus infecting yard long bean because it can decrease yield and seed transmitted. The aims of research were to determine the effect of plant age infected by BCMV on seed transmission efficiency of the virus, as well as its effect on plant growth. BCMV was mechanically inoculated on yard long bean at 1, 2, 3, and 4 weeks after planting (WAP). Observation was conducted for incubation period, disease incidence and severity, seed transmission efficiency of the virus, plant height, and productivity of the plants. Virus infection was detected using indirect ELISA method. The results showed that the earlier infection of BCMV occurred the shortest incubation period, the most severe symptoms, the highest inhibition of plant growth, and productivity. Disease severity was 94.6, 83.8, 81.1, and 69.6% on plants inoculated at 1, 2, 3, and 4 WAP, respectively. Disease incidence and virus titer was not affected by infection on different plant age. Seed transmission of BCMV was 7, 66, 39, and 24% on plants inoculated at 1, 2, 3, and 4 WAP, respectively. Infection on 2 WAP was considered the critical times for BCMV to be seed-borne on yard long bean.